An official European Respiratory Society statement: pulmonary haemodynamics during exercise. Issue 5 (23rd November 2017) - Kovacs, Gabor; Herve, Philippe; Barbera, Joan Albert; Chaouat, Ari; Chemla, Denis; Condliffe, Robin; Garcia, Gilles; Grünig, Ekkehard; Howard, Luke; Humbert, Marc; Lau, Edmund; Laveneziana, Pierantonio; et al.
There is growing recognition of the clinical importance of pulmonary haemodynamics during exercise, but several questions remain to be elucidated. The goal of this statement is to assess the scientific evidence in this field in order to provide a basis for future recommendations. Right heart catheterisation is the gold standard method to assess pulmonary haemodynamics at rest and during exercise. Exercise echocardiography and cardiopulmonary exercise testing represent non-invasive tools with evolving clinical applications. The term "exercise pulmonary hypertension" may be the most adequate to describe an abnormal pulmonary haemodynamic response characterised by an excessive pulmonary arterial pressure (PAP) increase in relation to flow during exercise. Exercise pulmonary hypertension may be defined as the presence of resting mean PAP <25 mmHg and mean PAP >30 mmHg during exercise with total pulmonary resistance >3 Wood units. Exercise pulmonary hypertension represents the haemodynamic appearance of early pulmonary vascular disease, left heart disease, lung disease or a combination of these conditions. Exercise pulmonary hypertension is associated with the presence of a modest elevation of resting mean PAP and requires clinical follow-up, particularly if risk factors for pulmonary hypertension are present. There is a lack of robust clinical evidence on targeted medical therapy for exercise pulmonary hypertension. Pulmonary haemodynamics during exercise provides relevant information on the lung, pulmonary vessels and heart http://ow.ly/EBOF30fuHWY